1991
DOI: 10.1016/0014-5793(91)80489-p
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the phosphorylation sites in elongation factor‐2 from rabbit reticulocytes

Abstract: The sites in ~ukaryolic elongation factor eEF-2 phosphorylated by the Ca~*tcalmodulin.depcnd¢nt dZF.2 ktnas© in vitro have been identified, The kinase eatalysed the rapid mcorperation of one real ol'phosphate par real cEF.2 .nd the slower incorporation of a second mol. All the phosphorylation sit,:s in eE F-2 are contained in the CN Br fragment ¢orrespondinil to residues 22~ 155. TP/ptie discstion cf phosphorylnted QEF.2 yielded 3 phospkopeptides, one being tlnique to monophosphoryl~ted eF.F.2, The phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 32 publications
(22 reference statements)
2
66
0
Order By: Relevance
“…We found one peak consistent with a phosphorylation on the tryptic peptide FTDTR, corresponding to residues 55-59 of rat eEF-2 (Supplementary Figure 2b). This site matches exactly with a previously described phosphorylation site on eEF-2 22,36,37 and suggests that our DIGE experiment had detected a salinduced phosphorylation of eEF-2. We confirmed that sal eEF-2 phosphorylation and ER stress M Boyce et al induces eEF-2 phosphorylation, using an immunoblot for phosphorylated Thr56, the major site of eEF-2 phosphorylation in vivo.…”
Section: Resultssupporting
confidence: 91%
“…We found one peak consistent with a phosphorylation on the tryptic peptide FTDTR, corresponding to residues 55-59 of rat eEF-2 (Supplementary Figure 2b). This site matches exactly with a previously described phosphorylation site on eEF-2 22,36,37 and suggests that our DIGE experiment had detected a salinduced phosphorylation of eEF-2. We confirmed that sal eEF-2 phosphorylation and ER stress M Boyce et al induces eEF-2 phosphorylation, using an immunoblot for phosphorylated Thr56, the major site of eEF-2 phosphorylation in vivo.…”
Section: Resultssupporting
confidence: 91%
“…eEF2 is phosphorylated at Thr56 by eEF2 kinase (eEF2K), impairing its interaction with the ribosome and thus inactivating elongation. 64 The activity of eEF2K can be regulated by S6 kinases. 35 Phosphorylation of eEF2K at Ser366 by S6Ks impairs its activity and hence favors activation of translation.…”
Section: Discussionmentioning
confidence: 99%
“…eEF-2 is the sole substrate of this kinase and does not appear to be phosphorylated by any other kinase (Mitsui et al, 1993;. Three threonyl residues located at the NH 2 terminus of eEF-2 can be phosphorylated by eEF-2 kinase in vitro (Ovchinnikov et al, 1990;Price et al, 1991;. Phosphorylation of Thr 56 alone seems to be responsible for the inhibition of mRNA translation in various cell-free systems Ryazanov et al, 1988;.…”
Section: Abstract: Elongation Factor-2; Phosphorylation; Calcium; Prmentioning
confidence: 99%